Perlakuan Pupuk Kandang Ayam terhadap Pertumbuhan dan Hasil Tanaman Segau Varietas Ensabi dan Lokal (Dayak) di Tanah Berpasir: Effect of Chicken Manure Fertilizer on the Growth and Yield of Segau Plants of Ensabi and Local (Dayak) Varieties in Sandy Soil - Hidayati, Nurul; Rosawanti, Pienyani; Ardiyanto, Ahmad; Susilo, Djoko Eko Hadi; Arfianto, Fahruddin; Hariyadi, Hariyadi (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This research aimed to analyze the interaction between chicken manure fertilizer dosage treatment and variety treatment, as well as their individual factors, on the growth and yield of Ensabi and local segau plants in sandy soil. The research was conducted for 4 months at the Experimental Garden of the University of Muhammadiyah Palangkaraya. This polybag research used a Randomized Block Design (RBD). Factor I: chicken manure fertilizer dosage treatment (A) consisted of 5 levels, namely: A1= 5 t ha-1, A2= 10 t ha-1, A3= 15 t ha-1, A4= 20 t ha-1, and A5= 25 t ha-1, and Factor II: segau/Dayak mustard variety treatment (V), namely: Ensabi segau variety (V1) and local segau variety (V2).The results showed that the interaction between chicken manure fertilizer dosage treatment and local segau variety had a significant effect on the variable of leaf number at 21 days after planting (DAP). The treatment of 25 t ha-1 chicken manure fertilizer with the local segau variety (V2A5) resulted in the highest leaf number, which was 13.33 leaves, but was not significantly different from other treatments, except for the Ensabi variety with 5 t ha-1 chicken manure fertilizer (V1A1) which resulted in 8.00 leaves. The single treatment of chicken manure fertilizer dosage had a significant effect on the variables of leaf number at 21 DAP and shoot weight at 21 DAP. The single treatment of segau variety had a very significant effect on the variables of leaf area at 14 DAP and 21 DAP, and shoot weight at 21 DAP (at harvest). The segau variety treatment did not have a significant effect on plant height at 14 DAP and 21 DAP, leaf number at 14 DAP and 21 DAP, root length, and plant fresh weight. The research results indicate that the local variety is more efficient to be planted on sandy soil with a chicken manure fertilizer dosage of 5 t ha-1. Keywords : Ensabi, Dayak mustard, chicken manure fertilizer dosage, segau, sandy soil